Computationally-efficient rendering of diffuse reflections for geometrical acoustics based room simulation - Ewert Stephan D.; Gößling Nico; Buttler Oliver; van de Par Steven; Hu Hongmei (Acta Acustica)
Geometrical acoustics is well suited for real-time room acoustics simulation and is often implemented using the image source model (ISM). One drawback of the ISM is its limitation to specular reflections, while sound scattering plays an important role in real environments. Here, computationally-efficient, digital-filter approximations are proposed to account for effects of non-specular scattered reflections in the ISM. For scattering at large surfaces such as room boundaries, each reflection is energetically split into a specular and a scattered part, based on the scattering coefficient. The scattered sound is coupled into a diffuse reverberation model. Temporal effects of the underlying surface scattering for an infinite ideal diffuse (Lambertian) reflector are derived and the resulting monotonic decay is simulated using cascaded all-pass filters. Effects of scattering and multiple (inter-) reflections caused by larger geometric structures at walls, and by objects in the room are accounted for in a highly simplified manner. A single parameter is used to quantify deviations from an empty shoebox room. The cumulated temporal effect of scattering along a reflection path is mimicked using cascaded all-pass filters adjusted to obtain a gamma-distribution-shaped envelope. The proposed method was perceptually evaluated with both music and pulse stimuli against dummy head recordings of real rooms. The results show a better agreement between the recording and the simulation for transient stimuli. In a technical evaluation, the temporal evolution of echo density showed a comparable profile for the suggested method and real rooms.